MUTU MIKROBIOLOGI DAN ORGANOLEPTIK DENDENG ITIK PETELUR AFKIR PADA BERBAGAI WAKTU KYURING DAN KONSENTRASI GARAM DAPUR - Supamri, Supamri (JSTT, 2015)
The fresh meat is easy to damage due to the change of chemical and microbiological contamination. This study aims to determine the quality of microbiological and organoleptic quality jerky laying ducks curing rejects at various times and concentrations of salt. The Experiments used completely randomized factorial design with two factors: the first factor, the time of curing (C) consists of 15 hours (C1), 20 hours (C2), 25 hours (C3) and 30 hours (C4). The second factor was the concentration of salt (B) consisting of: 5% (G1) and 10% (G2). Each treatment was repeated 2 times therefore there are 16 units experimental treatment. Variables observed included: 1) Test microbiology (TPC) and 2) the organoleptic test. The results showed that the interaction of treatment time and the salt concentration significantly affected to the appearance, aroma and taste, while the color and quality of microbiological have no real effect. Microbiological quality of the treatment time curing for 30 hours (C4) was not significantly different on the total microbial jerky laying ducks culled but gave the lowest total of microbial namely 1'5 x106 compared to another treatments. Organoleptic quality test showed that the best combination of treatment was that the curing time for 25 hours with the salt concentration 10% (C3G2) on the appearance, aroma, color and flavor with the average value 5 (like category).